Projeto experimental de colaboração entre a produção audiovisual do TCE-PB e de estudantes da rede pública - Gonçalves, Sandro; Souza, Helder Bruno A. M. de; Carolino, Fábia; Kulesza, Raoni; Toscano, Rafael M.; Becker, Valdecir (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
This paper describes an experimental videocolaboration project that integrates productions of institutional videos from the Court of Auditors of the State of Paraíba (TCE-PB) to non-professional production provided by public school students. Public school students are invited by teachers to produce videos before meeting TCE-PB’s facilities. This content production feeds two applications: a collaborative map and a lecture support system. The last one focuses on assisting the institution's staff to deliver presentations at the Court's auditorium in the preparation of customized materials for each school visit. During the preparation process, the speaker can include in his presentation videos produced by students and available in a public database. Finally, the system gathers the video files, school data, and students participating in the auditorium dynamics into a single media that can be played and shared at the end of the event. This research is based on and uses Audiovisual Design workflow as a methodological route.